Transcatheter Edge‐to‐Edge Repair for Severe Mitral Regurgitation in Patients With Cardiogenic Shock: A Systematic Review and Meta‐Analysis - Kyriakos Dimitriadis; Stergios Soulaidopoulos; Nikolaos Pyrpyris; Μarios Sagris; Konstantinos Aznaouridis; Eirini Beneki; Panagiotis Theofilis; Panagiotis Tsioufis; Fotis Tatakis; Christos Fragkoulis; Mony Shuvy; Christina Chrysohoou; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Patients with severe mitral regurgitation and cardiogenic shock demonstrate a poor prognosis. Mitral transcatheter edge‐to‐edge repair could alter patient management. Methods and Results We systematically reviewed PubMed/Medline, Scopus, and Cochrane Library until January 2023, including studies assessing transcatheter edge‐to‐edge repair in patients with severe mitral regurgitation and cardiogenic shock. Studies with <5 patients were excluded. The primary outcome was device success and all‐cause death, while secondary outcomes included myocardial infarction, stroke, and heart failure hospitalization rates at 30‐day and intermediate‐term follow‐up. A fixed‐effects meta‐analysis was used to estimate pooled rates. Risk of bias was assessed with the Newcastle–Ottawa Scale. A total of 24 studies and 5428 patients were included, with a mean age of 71.2±3.3 years and a high mean Society of Thoracic Surgery score (15.2±8.9). Device success was achieved in 86% (95% CI, 85%–87%) and mitral regurgitation ≤2+ in 89% (95% CI: 88%–90%). The 30‐day all‐cause mortality rate was 14% (95% CI, 13%–15%). Stroke, myocardial infarction, and heart failure hospitalization rates were 2% (95% CI, 1%–2%), 15% (95% CI, 13%–18%), and 9% (95% CI, 8%–10%), respectively. Patients with acute myocardial infarction had similar device success (81% [95% CI, 74%–87%]), a 30‐day mortality rate of 20% (95% CI, 16%–25%), and intermediate‐term mortality rate of 14% (95% CI, 9%–19%). In non–myocardial infarction populations, the 30‐day mortality rate was 13% (95% CI, 13%–14%), and the intermediate‐term mortality rate was 35% (95% CI, 34%–36%). Conclusions In patients with mitral regurgitation and cardiogenic shock, transcatheter edge‐to‐edge repair is associated with favorable 30‐day and intermediate‐term outcomes. Limitations, including the observational design of included studies and considerable heterogeneity, necessitate further research in this setting.